The second life of micro-organisms. Bio-digital design for a new ecology of space and behaviour - Alessandro Valenti; Claudia Pasquero (Agathón, 2021)
To reflect today, as designers and researchers, on the issue of Second Life, is to pose questions not only about the potential contemporary articulations of the term within a disciplinary field defined by knowledge that intertwines sectors like Urbanism, Architecture, Interior Design and Design but also to explore the very concept of life rendering living organisms – both human and not – as an active part of the speculation and the eventual experimentations giving new meaning to actions like regeneration or reuse. To do so, it is necessary to amplify the range of intervention and to engage other disciplines like biology and computer science, but also philosophy, anthropology and many more. An example of this practice is systemic design, a method defined by the combination and integration of systemic thought, computational design, biotechnology and prototyping. It is an extended approach to design – ranging from the micro to macro – incorporated in applications where projects and installations become interactive laboratories based on interspecies collaboration. A testament to this approach is the work carried out by a multidisciplinary entity like ecoLogicStudio, through theory and practice.